Non-canonical Glucocorticoid Receptor Transactivation of gilz by Alcohol Suppresses Cell Inflammatory Response - Ng, Hang Pong; Jennings, Scott; Wang, Jack; Molina, Patricia E.; Nelson, Steve; Wang, Guoshun (Frontiers in Immunology, 2017)
Acute alcohol exposure suppresses cell inflammatory response. The underlying mechanism has not been fully defined. Here we report that alcohol was able to activate glucocorticoid receptor (GR) signaling in the absence of glucocorticoids (GCs), and upregulated glucocorticoid-induced leucine zipper (gilz), a prominent GC-responsive gene. Such a non-canonical activation of GR was not blocked by mifepristone, a potent GC competitor. The proximal promoter of gilz, encompassing five GC-responsive elements (GREs), was tested in a luciferase reporter system. Deletion and/or mutation of the GREs abrogated the promoter responsiveness to alcohol. Thus, the GR-GRE interaction transduced the alcohol action on gilz. Alcohol induced GR nuclear translocation, which was enhanced by the alcohol dehydrogenase inhibitor fomepizole, suggesting that it was alcohol, not its metabolites, that engendered the effect. Gel mobility shift assay showed that unliganded GR was able to bind GREs, and such interaction withstood clinically-relevant levels of alcohol. GR knockout via CRISPR/Cas9 gene targeting or GILZ depletion via small RNA interference diminished alcohol suppression of cell inflammatory response to LPS. Thus, a previously unrecognized, non-canonical GR activation of gilz is involved in alcohol modulation of cell immune response.